High levels of alexithymia in patients with multiple sclerosis - Eboni, Audred Cristina Biondo (Dement Neuropsychol, 2018)
Alexithymia is a personality trait characterized by difficulties identifying and describing feelings. Some researchers describe high levels of alexithymia among patients with multiple sclerosis (MS) but literature data on this subject are scarce. OBJECTIVE: The objective of the present study was to characterize findings of alexithymia in patients with MS. METHODS: This cross-sectional case-control study included 180 patients with MS and a matched control group. Data for patients with MS included disease duration, number of demyelinating relapses and degree of neurological disability, as assessed by the Expanded Disability Scale Score (EDSS). In addition, the Hospital Anxiety and Depression (HAD) scale and the Toronto Alexithymia Scale (TAS) were used. RESULTS: There were 126 women and 54 men in each group, with median age of 37 years and median education of 16 years. Patients with MS had higher degrees of depression (p<0.01), anxiety (p=0.01) and alexithymia (p<0.01) than did control subjects. For individuals with MS, depressive traits (p<0.01), anxious traits (p=0.03), higher age (p=0.02), lower education level (p=0.02), higher degree of disability (p<0.01) and not being actively employed (p=0.03) were associated with higher rates of alexithymia. CONCLUSION: Alexithymia was a relevant finding in patients with MS.